Bahasa Indonesia: english - Wisuda, Nova Laili; Wongloom, Prisana (Plant Protection Department, Faculty of Agriculture, Universitas Andalas, 2020)
The Good Agriculture Practices (GAP) has been practiced in many countries, including Thailand. This study aimed to examine the GAP system's effect on pest arthropods' diversity and their natural enemies in the early generative period of rice cultivation in Phattalung Province, Thailand. The research was conducted in the rice fields of Pradoo Reang Village, Phattalung Province, Southern Thailand. Sampling was carried out using the selected method with a diagonal separation direction and repeated three times. Diversity, evenness, and dominance of pests and natural enemies were determined using the Shannon Wiener index, Evenness index, and Simpson index. The results showed that the pest population found in lowland rice fields planted with the GAP cultivation system was lower than conventional, but with a higher natural enemy population. Pest arthropods in the GAP cultivation system had a higher diversity index compared to conventional, with moderate pest evenness and similarity indexes. Arthropods that act as natural enemies in the GAP cultivation system had a moderate diversity index, with a higher evenness index than conventional, and a moderate similarity index. The two highest of herbivores were Nephotettix virescens and Leptocorisa oratorius, and the two highest of natural enemies were Verania discolor and Agriocnemis sp.Keywords: Agroecosystem, Arthropods, organic, sustainable agriculture